Phylogenetic position of Sphincterodiplostomum Dubois, 1936 (Digenea: Diplostomoidea) with description of a second species from Pantanal, Brazil. (11th February 2021) - Achatz, T.J.; Bell, J.A.; Melo, F.T.V.; Fecchio, A.; Tkach, V.V.
Abstract: Sphincterodiplostomum is a monotypic genus of diplostomid digeneans that parasitize fish-eating birds in the neotropics. The type species Sphincterodiplostomum musculosum has a unique, dorsal, tubular invagination in the opisthosoma with a muscular sphincter. Whereas larvae of S. musculosum are relatively commonly reported in Neotropical fish helminth surveys, adult specimens from birds are rarely collected. Prior to our study, no DNA sequence data for S. musculosum were available. Our molecular and morphological study of mature and immature adult Sphincterodiplostomum specimens from three species of birds and one species of crocodilian revealed the presence of at least two species of Sphincterodiplostomum in the neotropics. We provide the first molecular phylogeny of the Diplostomoidea that includes Sphincterodiplostomum . In addition, this is the first record of S. musculosum from caimans, along with the first record of fully mature adult S. musculosum from green kingfisher Chloroceryle americana . The new species of Sphincterodiplostomum ( Sphincterodiplostomum joaopinhoi n. sp.) can be morphologically distinguished from S. musculosum based on the anterior extent of vitelline follicles, narrower prosoma, substantially smaller holdfast organ and structure of tegumental spines. Our data revealed 0.7% interspecific divergence in 28S and 10.6–11.7% divergence in cox 1 sequences between the two Sphincterodiplostomum species.